Influence of р-thyrozol on the morphology and antioxidant-prooxidant balance in prostate of rats at sulpiride-induced benign prostatic hyperplasia - T. G. Borovskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The aim of the research was to study the influence of p-thyrozol on the morphology and antioxidant-prooxidant balance in prostate of rats at sulpiride-induced benign prostatic hyperplasia. It was found that introduction of p-thyrozol promoted thwarting progress of pathological process that was proved by less degree of manifestation of proliferative processes in epithelium and of cellular infiltration of stroma. In addition, increase of antioxidant reserve of gland was registered.